Navigating organizational excellence: a comparative study and roadmap for streamlining defense infrastructure organizational model of Georgia - Ivan OKROMTCHEDLISHVILI (Bulletin of "Carol I" National Defense University, 2024)
In the face of evolving geopolitical dynamics and increasing security challenges, the efficacy of a nation’s defense infrastructure is pivotal. This article conducts a comprehensive exploration of defense infrastructure organizational models, centering on the United Kingdom, France, Germany, Australia, and Latvia. Through a meticulous comparative analysis, the study delves into organizational structures, international operations, responsibilities, and strategic focuses of these nations’ defense infrastructure entities. The goal is to glean insights applicable to Georgia’s unique context, identifying key differences and commonalities to formulate a strategic roadmap for enhancing its defense infrastructure capabilities. The article examines each country’s defense infrastructure model, highlighting distinctive features in organizational structure, international operations, responsibilities, and strategic focus. Drawing upon these insights, the study proposes tailored recommendations for Georgia, spanning organizational structure, international operations, responsibilities and focus, modernization and strategy, and integration of departmental efforts. Key entities within Georgia’s defense infrastructure organizational model, such as the Department of Defense Sustainability, the J-4 Logistics Planning Department, and the Command for Logistics Support of the Troops, are illuminated to underscore their pivotal roles in fortifying the country’s defense capabilities. Concluding with the identification of key areas for improvement in Georgia’s defense infrastructure organization, the article outlines recommendations encompassing organizational structure, international operations, responsibilities and focus, modernization and strategy, and integration of departmental efforts. By aligning Georgia’s defense infrastructure with international best practices, the nation can enhance security, contribute to regional stability, and actively participate in global security efforts. In essence, this article serves as a strategic guide for Georgia, offering a roadmap to fortify its defense infrastructure in a rapidly changing world. Through a synthesis of global insights and tailored recommendations, Georgia can position itself as a resilient and adaptable force, safeguarding national interests and contributing to a more secure global landscape.